Therapeutic Management of Hypothyroidism in Dogs - Nagella Naveen; N. Lakshmi Rani; K. Basava Reddy; V. Devi Prasad (The Indian Veterinary Journal, 2025)
The present study was conducted at Veterinary Clinical Complex of NTR College of Veterinary Science, Gannavaram, from March to November 2023,found a hospital prevalence of hypothyroidism at 0.45% (27/5957).Ten hypothyroid dogs (Group II) treated with Levothyroxine (0.02 mg/kg daily) had significantly (p<0.01) lower pre therapeutic mean TT4 (8.42±1.15 nmol/L) and FT4 (0.37±0.09 ng/dL) levels compared to healthy controls (Group I), with significant (p≤0.01)improvement after therapy. Haemato-biochemical analysis revealed significant increase (p<0.05) in haemoglobin, PCV and TEC, along with significant (p<0.05)decline in ALP, cholesterol and triglyceride levels after therapy, emphasizing the importance of levothyroxinein canine hypothyroidism.